Local anaesthesia for major general surgical procedures. A review of 116 cases over 12 years. Issue 844 (February 1996) - Dennison, A.; Oakley, N.; Appleton, D.; Paraskevopoulos, J.; Kerrigan, D.; Cole, J.; Thomas, W. E.
Abstract : Between 1980 and 1992, 116 patients had either a simple mastectomy (32) or intra-abdominal procedures (84) under local anaesthesia (0.5-1% lignocaine with 1:200 000 adrenaline). A wide variety of general surgical procedures were feasible using only supplementary intravenous sedation (54%). Complications were uncommon and related to surgical procedure (three incorrect diagnoses, three procedures impossible) rather than the anaesthetic technique. There were no anaesthetic toxicity or postoperative problems. Local anaesthesia is extremely safe and facilitates larger surgical procedures than is generally appreciated.